A comparison of sublingual with vaginal administration of misoprostol for induction of labor at term - Akare, Monika D.; Patel, Purvi K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To compare the efficacy and safety of sublingual route of misoprostol with vaginal route of administration. Methods: This study was conducted at Department of Obstetrics and Gynecology, Medical College, Baroda, Gujarat, India. 50 cases each with a singleton term pregnancy and a live fetus requiring induction of labor were allocated to sublingual and vaginal administration of misoprostol. Outcome measures related to labor and maternal and fetal side effects were compared between the 2 groups and evaluated using Chi square test and relative risk (RR) with 95% confidence intervals (CI). Results: The sublingual route of misoprostol was associated with a reduced risk of failed induction, reduced time from initiation to induction, reduced induction to delivery interval and a higher incidence of maternal and fetal side effects. However, the differences were not statistically significant. Conclusions: The sublingual route of administration of misoprostol is comparable in efficacy and safety to the vaginal route for induction.